The Implementation of Teaching Speaking Using Think Talk Write (TTW) Strategy at the Third Level of Institut Prima Bhakti Pamekasan - Hanifatur Rizqi; Eko Adi Sumitro (International Journal of Educational Narratives, 2024)
Background. In teaching learning process of English courses, the teachers have an important role because they are the influential people in the class and students can learn from the teachers, while the teachers have to provide suitable learning system by using interesting instruction of the material and good method as a strategy to interest students. Think Talk Write (TTW) Strategy is one of the alternative methods in teaching learning process to increase students’ understanding and communicating that is based on comprehension that study is a social behavior. Therefore, this title is expected to inform about the implementation of Think Talk Write (TTW) Strategy in teaching learning English process especially in teaching speaking Purpose. The researcher is interested to conduct the research for students at the third level of Institut Prima Bhakti Pamekasan in which an English teacher implements TTW Strategy in teaching speaking. The problems investigated in this study were the way to implement, the difficulties that faced by students and the ways to solve the students’ difficulties in teaching speaking using Think Talk Write (TTW) Strategy. Method. In obtaining the data, the researcher used descriptive qualitative to describe all of the result of research and the data were gotten by observation to see the teaching speaking process in the class, interview to get supporting data and documentation as a proof to study the data. This research had done five times. The first, it was done on 27th September 2023, the second on 28th September 2023, the third on 5th October 2023, the fourth on 12th October 2023, and the fifth on 19th October 2023. Results. The result of the study showed that in the implementation of teaching speaking used TTW strategy at the third level of Institut Prima Bhakti Pamekasan, the teacher introduced the topic at the first and asked the students to answer the problem of the topic individually (think phase), then discussed the topic in a group (talk phase) and wrote the result of discussion individually. The last, the teacher asked the students to present their answer to the other group that possible for other group gave consideration. Conclusion. The students’ difficulties were they difficult to have understanding about the topic because they had no experience, they difficult to make sentences because they had little vocabularies and relate their opinion with other friends’ opinion in a group (talk phase).